Dejerine-Sottas disease: a case report - Marinho, Jaqueline Luvisotto (2003)
CONTEXT: Hereditary peripheral neuropathies (hereditary motor-sensory neuropathies or hereditary demyelinating neuropathies) are abnormalities of Schwann cells and their myelin sheaths, with peripheral nerve dysfunction. They include Charcot-Marie-Tooth disease, Dejerine-Sottas disease, congenital hypomyelinating neuropathy and hereditary neuropathy with liability to pressure palsy. OBJECTIVE: The objective of the present work was to describe a case of Dejerine-Sottas disease. CASE REPORT: A 9-year-old boy presented progressive slight motor deficit in the lower limbs, particularly in the feet, and generalized hyporeflexia. Electromyography disclosed significant reduction in motor and sensory nerve conduction velocities. Sural nerve biopsy showed axons surrounded by a thin myelin sheath and concentrically arranged cytoplasmic processes of Schwann cells forming onion-bulbs. No axon damage was observed.